The Influence Of The Arabic Language On Legal Terminology: The Term Hisbah As A Case Study/ تأثير اللغة العربية في المصطلحات الشرعية: مصطلح الحسبة نموذجاً - Alabri, Khalid Hassan (Ijaz Arabi Journal of Arabic Learning, 2025)
This research explores one of the fundamental principles of terminology and the extent of the Arabic language’s influence on Islamic legal terms. It focuses on Hisbah, which has become widely associated with "enjoining good and forbidding evil." Moreover, this research highlights the significant linguistic legacy found in the literature of hisbah, especially in practical manuals that described the duties of the hisbah authority. This study uses a descriptive approach, which is based on the description of phenomena that help understand and identify important aspects of the best way to correct student errors. Data collection techniques use observation and documentation. In addition, it links the verses of the Quran mentioned in the study with their context in the Quran and authenticates the hadith from the source. These works not only documented the actions of the muhtasib (market inspector or moral enforcer), but also served as guides for implementation. They employed specific expressions, phrases, and terms that later influenced Arabic lexicography. The influence of Arabic on Islamic terminology and the relationship between linguistic vocabulary Hisbah as a term is an example and model that explains this influence, relationship, and combination. It is a term used to refer to a person who performs the amar ma'ruf nahi munkar function. The word “Hisbah” does not appear in the Qur'an or Sunnah as a term used to indicate a Muslim's duty to amar ma'ruf nahi munkar. Hisbah has several meanings in language: asking for reward, denying, management, and consideration. You say: So and so has good hisbah, meaning he has good management, sufficiency, and consideration.